Associations between residual hyperarousal and insomnia symptoms in veterans following a 2‐week intensive outpatient program for posttraumatic stress disorder. Issue 2 (22nd November 2021) - Tanev, Kaloyan S.; Lynch, Elyse A.; Blackburn, Allyson M.; Terry, Douglas; Goetter, Elizabeth M.; Wright, Edward C.; Gupta, Carina; Stasko, Cory E.; Spencer, Tom
Abstract: Many returning military service members and veterans who were deployed following the September 11, 2001, terrorist attacks (9/11) suffer from posttraumatic stress disorder (PTSD) and insomnia. Although intensive treatment programs for PTSD have shown promise in the treatment of PTSD symptoms, recent research has demonstrated that sleep disturbance shows little improvement following intensive trauma‐focused treatment. The aim of the present study was to evaluate changes in self‐reported insomnia symptoms among veterans and service members following participation in a 2‐week intensive program for PTSD. We further aimed to investigate if residual PTSD symptoms, specifically hyperarousal, were associated with residual insomnia symptoms. Participants ( N = 326) completed self‐report assessments of insomnia, PTSD symptoms, and depressive symptoms at pre‐ and posttreatment. At pretreatment, 73.9% of participants ( n = 241) met the criteria for moderate or severe insomnia, whereas at posttreatment 67.7% of participants ( n = 203) met the criteria. Results of paired t tests demonstrated statistically significant differences between pre‐ and posttreatment Insomnia Severity Index scores; however, the effect size was small, d = 0.34. Analyses revealed that posttreatment hyperarousal symptoms were associated with posttreatment insomnia. These findings suggest that although an intensive program for service members and veterans with PTSD may significantly reduce insomnia symptoms, clinically meaningful residual insomnia symptoms remain. Further research is warranted to elucidate the association between residual hyperarousal and insomnia symptoms following intensive trauma‐focused treatment.